The prevalence and correlates of falls in adults with attention-deficit/hyperactivity disorder: cross-sectional study - Alkhalidi, Maraheb M.; Lein, Donald H.; Alotaibi, Mansour M. (Frontiers in Psychiatry, 2025)
BackgroundFalls are a major concern due to potentially causing injuries and long-term disabilities. Studies have shown that individuals with Attention-Deficit/Hyperactivity Disorder (ADHD) have decreased balance. Poor balance is associated with increased risk of falls. Limited studies have investigated the risk of falls among adults with ADHD despite the increasing prevalence of ADHD world-wide.ObjectiveThis study aimed to estimate the prevalence of falls and fall-related injuries, as well as to explore correlates of falls among adults with ADHD during off- and on-medication status.MethodsAdults with ADHD were recruited for this cross-sectional analysis. Participants completed two sessions (an off-medication and an on-medication session). A customized questionnaire was used to collect relevant data, including demographic information, psychostimulant medication use, fall history, and fall risk. Further, ADHD symptoms were assessed using the Adult ADHD Self-Report Scale-5. Participants completed body mass (kg) and body height (cm) measure on the first session. Participants also completed several measures of physical function, including maximum voluntary contraction (MVC [N.m]) and passive range of motion (ROM [°]) static balance assessment on a force platform (sway area [cm2] and sway velocity [cm/s]), Timed Up and Go test (TUG[s]) and the Lateral Step-Up Test (LSUT; [repetitions]). Prevalence of falls was estimated using frequency data. Associations of fall factors among adults with ADHD were evaluated using chi-square tests and Spearman’s correlation.ResultsForty-five adults (35 women; mean age = 28.4 ± 6.3 years) were enrolled in the study. The 12-month prevalence of falls among adults with ADHD was 37.8%. Fallers were significantly more likely to feel unsteady (62.5%), and 77.8% expressed worry about falling compared to non-fallers. The higher prevalence of falls observed among adults with the combined subtype of ADHD (46.7%). The SLEC score, PROM, TUG, and PMVC demonstrated insignificant correlation with falling in adults with ADHD during off- and on-medication status (rs = <0.25, p > 0.05); thus, regressions analysis for these potential correlates were not performed.ConclusionsAdults with ADHD exhibited increased fall rates. Biological sex, ADHD subtype, perceived feeling of unsteadiness, and worries about falling were associated with falls in this population.